CoMo/SS Cathode Catalyst for Enhanced Hydrogen Production in Microbial Electrolysis Cells - Lei, Gao; Wang, Yaoqiang; Xiao, Gang; Su, Haijia (Catalysts, 2025)
Hydrogen energy has emerged as a pivotal clean energy solution due to its sustainability and zero-emission potential. Microbial electrolysis cells are a promising technology for renewable hydrogen production, typically relying on expensive and unstable Pt/C catalysts for the hydrogen evolution reaction (HER). To address these limitations, this study develops a cost-effective and durable alternative approach. A cobalt–molybdenum (Co-Mo) alloy catalyst (denoted as CoMo/SS) was synthesized via a one-step electrodeposition method on 1000-mesh 316L stainless steel at a current density of 30 mA·cm−2 for 80 min, using an electrolyte with a Co-to-Mo ratio of 1:1. The electrochemical properties and hydrogen evolution performance of this catalyst in a microbial electrolysis cell were evaluated. Key results demonstrate that the CoMo/SS catalyst achieves a good catalytic performance of hydrogen evolution. The CoMo/SS cathode catalyst only requires an overpotential of 91.70 mV (vs. RHE) to reach a current density of 10 mA·cm−2 in 1 mol·L−1 KOH, with favorable kinetics, evidenced by a reduced Tafel slope of 104.10 mV·dec−1, enhanced charge transfer with a charge transfer resistance of 4.56 Ω, and a double-layer capacitance of 34.73 mF·cm−2. Under an applied voltage of 0.90 V, the CoMo/SS cathode exhibited a hydrogen production rate of 1.12 m3·m−3·d−1, representing a 33.33% improvement over bare SS mesh. This performance highlights the catalyst’s potential as a viable Pt/C substitute for scalable MEC applications.